KAJIAN AKADEMIK PENANGGULANGAN KEMISKINAN DI KOTA PAGAR ALAM - Fachrizal Bachri (Department of Development Economics, Universitas Sriwijaya, 2010)
This academic exercise explained the poverty phenomenon in Pagar Alam city, South Sumatra province. It tries also to elaborate the causes of poverty and poverty alleviation programs implemented by Local Government. Opportunities to alleviate poverty and improve well-being depend on the supporting environment. The ability of poor people should Â be harnessed and strengthened. In addition, the Government should create an institutional framework that supports the strategy of self-improvement and sustainable welfare. Local governments, the private sector, and together with the people have a big role to create such opportunities. Local Government is also obliged to control the private sector and enforce legal obligations, environmental, and social order to reduce the negative impact of business practices on the environment, and maximize the benefits for society. Vulnerability also needs to be reduced. This can be done with the use of the function of social safety nets such as free health insurance, free education and food subsidy. To improve the welfare sector in the framework of decentralization include macro and micro perspectives. From the macro side, it takes a synergistic cooperation between central governments, provincial governments including city government and private sector. Whereas from the micro side, it is to increase the monitoring and planning activities. This means to improve infrastructure and services, to maintain the subsidy system, to improve Â the natural environment including the economic environment, the social environment, and Â the political environment Keywords: Poverty, Policy, Welfare